On-Surface Evolution of meso-Isomerism in Two-Dimensional Supramolecular Assemblies - Park, Juyeon; Kim, Ju Hyung; Bak, Sunmi; Tahara, Kazukuni; Jung, Jaehoon; Kawai, Maki; Tobe, Yoshito; Kim, Yousoo (Angewandte Chemie - International Edition, 2019)
Chiral structures created through the adsorption of molecules onto achiral surfaces play pivotal roles in many fields of science and engineering. Here, we present a systematic study of a novel chiral phenomenon on a surface in terms of organizational chirality, that is, meso-isomerism, through coverage-driven hierarchical polymorphic transitions of supramolecular assemblies of highly symmetric π-conjugated molecules. Four coverage-dependent phases of dehydrobenzo[12]annulene were uniformly fabricated on Ag(111), exhibiting unique chiral characteristics from the single-molecule level to two-dimensional supramolecular assemblies. All coverage-driven phase transitions stem from adsorption-induced pseudo-diastereomerism, and our observation of a lemniscate-type (∞) supramolecular configuration clearly reveals a drastic chiral phase transition from an enantiomeric chiral domain to a meso-isomeric achiral domain. These findings provide new insights into controlling two-dimensional chiral architectures on surfaces.
Keywords: Chiral phase transitions; Conjugated molecules; Polymorphic transitions; Science and engineering; Single molecule level; Supramolecular assemblies; Surface evolution; Two-dimensional supramolecular assemblies; chirality; nanostructures; scanning tunneling microscopy; self-assembly; surface chemistry